MOSTI study on diversity - The Star, (2009)
The Institute of Tropical Forestry and Forest Products (INTROP) of universiti Putra Malaysia (UPM) has joined hands with the Ministry of Science, Technology and Innovation Malaysia (MOSTI) in a programme called Brain Gain Malaysia, with a project called Control of Diversity and the Carbon Balance of Tropical Forest.